The potential of energy substitution in the industrial sector - Abd. Aziz, Azlina (2007)
The extent of substitutability between energy and the other factors (i.e. labour and capital) and between individual fuels (coal, electricity, natural gas and petroleum) is an extremely important question and quite central to energy policy, planning and analysis. This study considers the possibilities of energy substitution in the industrial sector of 5 major energy producers of the developing world (Brazil, China, India, Indonesia and Venezuela). The theoretical model utilized in the study is the two-stage trans-log cost function. The model is estimated using time series data over the period 1978 to 2003. The results indicate substantial inter-factor and inter-fuel substitutions are possible in the industrial sector. Substitution possibilities were found (1) between capital and labour, between capital and energy and between energy and labour in the inter-factor model and (2) for most combination's of fuel types in the inter-fuel model. This implies that there is some flexibility in energy policy options and energy utilization.